Study of the Behavioral Pattern in Type-2 Diabetic Mice Prepared by Introducing 10% and 15% Fructose Solution (Bangladesh Pharmaceutical Journal, 2024)
An  altered  behavioral  pattern  is  a  deliberate  fact  in  diabetic  conditions  that  could  be  induced  due  to  the consumption of foods rich in fructose content. The objective of this research was to develop a fructose-induced diabetic mice model to determine the behavioral changes. Swiss albino mice were involved in this study as the animal model which was subdivided into three groups (control, test groups 1 and 2). Diabetes was induced in test groups 1 and 2 by introducing 10% and 15% fructose solution orally for 8 weeks. After 8 weeks, behavioral tests including hole board test (HBT), tail suspension test (TST), elevated plus maze test (EMT), and forced swim test (FST)  were  performed  to  evaluate  the  behavioral  pattern.  Findings  indicated  that  test  group  1  showed  a considerable increase in body weight but only a minor increase in fasting blood glucose (FBG) level than the control group. Neither the behavioral studies for test group 1 stretch any substantial alteration. Whereas test group 2 showed a considerable increase in FBG level and body weight as well as in the behavioral tests. (HBT: 47.87% lower head dipping than the control group; TST: 90.85% higher immobility time than the control group; EMT: 58% lower exploration to open arm than the control group; FST: 38.64% less mobility time than the control group). The findings of the study illustrate that consumption of high concentrations of fructose for long term could have a positive correlation with the induction of type 2 diabetes along with the altered behavioral pattern.Bangladesh Pharmaceutical Journal 27(2): 158-163, 2024 (July)